2022
DOI: 10.1108/jstpm-04-2022-0077
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the intention and adoption of cashless payment methods among the young adults in Malaysia

Abstract: Purpose Cashless payment is gradually replacing physical currency in almost every financial transaction across the world. Even though cashless payment methods have been available in Malaysia since a decade ago, their usage has remained relatively low in comparison to other countries. This study aims to analyse the elements that affect the Malaysian youth’s adoption intention and actual use of cashless payment by extending the unified theory of acceptance and use of technology (UTAUT) model with two key factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In this study, a positive relationship was observed between performance expectancy, satisfaction, and the continued intention to adopt e-wallets, aligning with findings by (Oliveira et al, 2016;Munikrishnan et al, 2022). This reinforces the understanding of performance expectancy as a key driver of e-wallet adoption, thus contributing to the refinement of ewallet adoption models.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In this study, a positive relationship was observed between performance expectancy, satisfaction, and the continued intention to adopt e-wallets, aligning with findings by (Oliveira et al, 2016;Munikrishnan et al, 2022). This reinforces the understanding of performance expectancy as a key driver of e-wallet adoption, thus contributing to the refinement of ewallet adoption models.…”
Section: Discussionsupporting
confidence: 88%
“…Effort expectancy is crucial to shaping satisfaction and continued e-wallet adoption, validating hypothesis H2. Perceived security profoundly affects satisfaction and the continuous intention to adopt ewallets, mirroring results from prior studies (Munikrishnan et al, 2022;Oliveira et al, 2016). This study extends the understanding of the critical role of security in sustaining e-wallet usage, a vital aspect in the current digital age.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To the best of our knowledge, studies on mobile payments have examined users’ intention to adopt the said technology or their readiness levels in silo (Alalwan et al, 2017; Oliveira et al, 2016; Singh et al, 2020; Trinugroho et al, 2017). Malaysian-based studies have focused on various factors related to mobile payments, mainly based on UTAUT (Munikrishnan et al, 2022) and UTAUT2 (Suo et al, 2021). There is a need to explore the predictors for mobile payment readiness and acceptance in the country considering the uptake of mobile payment services is still low (Malaysian Communication and Multimedia Commission, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, youths are the ideal population for all studies that employ new technical advancements 27 . Likewise, age and gender as moderators are two key variables in diverse research, such as mobile payment 18 , cashless payment 28 , and gamification 29 . These studies have shown gender and age-based differences in technology acceptance, making it important to investigate their role in shaping the relationships between the key variables 16 .…”
Section: Introductionmentioning
confidence: 99%